Inhibition of myocardial reperfusion injury by ischemic postconditioning requires sirtuin 3-mediated deacetylation of cyclophilin D. (July 2015) - Bochaton, T.; Crola-Da-Silva, C.; Pillot, B.; Villedieu, C.; Ferreras, L.; Alam, M.R.; Thibault, H.; Strina, M.; Gharib, A.; Ovize, M.; Baetz, D.
Abstract: Rationale . How ischemic postconditioning can inhibit opening of the mitochondrial permeability transition pore (PTP) and subsequent cardiac myocytes death at reperfusion remains unknown. Recent studies have suggested that de-acetylation of cyclophilin D (CyPD) by sirtuin 3 (SIRT3) can modulate its binding to the PTP. Objective . The aim of the present study was to examine whether ischemic postconditioning (PostC) might activate SIRT3 and consequently prevent lethal myocardial reperfusion injury through a deacetylation of CyPD. Methods and results . Using hypoxia–reoxygenation (H/R) in H9C2 cells, we showed that SIRT3 overexpression prevented CyPD acetylation, limited PTP opening and reduced cell death by 24%. In vitro modification of the CyPD acetylation status in MEFs by site-directed mutagenesis altered capacity of PTP opening by calcium. Calcium Retention Capacity (CRC) was significantly decreased with CyPD-KQ that mimics acetylated protein compared with CyPD WT (871 ± 266 vs 1193 ± 263 nmoles Ca 2 + /mg protein respectively). Cells expressing non-acetylable CyPD mutant (CyPD-KR) displayed 20% decrease in cell death compared to cells expressing CyPD WT after H/R. Correspondingly, in mice we showed that cardiac ischemic postconditioning could not reduce infarct size and CyPD acetylation in SIRT3 KO mice, and was unable to restore CRC in mitochondria as it is observed in WT mice. Conclusions . Our study suggests that the increased acetylation of CyPD following myocardial ischemia–reperfusion facilitates PTP opening and subsequent cell death. Therefore ischemic postconditioning might prevent lethal reperfusion injury through an increased SIRT3 activity and subsequent attenuation of CyPD acetylation at reperfusion. Highlights: Ischemic postconditioning prevents lethal reperfusion injury. SIRT3 is important in ischemic postconditioning. Cyclophilin D acetylation level regulates the mitochondrial transition pore opening. SIRT3 De-acetylates CyPD and inhibits mitochondrial permeability transition pore opening.